2021
DOI: 10.1016/j.jort.2020.100358
|View full text |Cite
|
Sign up to set email alerts
|

“There will be mushrooms again” – Foraging, landscape and forest fire

Abstract: In this paper, we address the relevance of recreational foraging, picking berries and mushrooms, for developing connection to nature and what happens when that practice is interrupted by drastic landscape change. We use the site of the largest forest fire in modern Swedish history as a case to examining the relevance of foraging. In previous studies, positive associations have been observed between the activity of picking berries and mushrooms with landscape-identity prior to forest fires. The results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Nevertheless, they mentioned actions to increase the possibility of finding mushrooms in the forest, such as not throwing garbage or not starting fires. This perception is justified, since it has been proven that the mycobiota of a forest change after a fire; especially the amount of ectomycorrhizal fungi decreases [ 105 , 106 ], which are the ones that the Wixaritari prefer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they mentioned actions to increase the possibility of finding mushrooms in the forest, such as not throwing garbage or not starting fires. This perception is justified, since it has been proven that the mycobiota of a forest change after a fire; especially the amount of ectomycorrhizal fungi decreases [ 105 , 106 ], which are the ones that the Wixaritari prefer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that foraging is often a family tradition learned from parents or grandparents and that childhood exposure is essential to the practice and knowledge of food foraging. In addition, foraging traditions and culture shape memories, identity, and a sense of cultural belonging [15,16]. Food foraging, as a practice, allows these foragers to adapt in the U.S., and simultaneously feel connected to their country of origin [17].…”
Section: Introductionmentioning
confidence: 99%